Performance of orangefin labeo, Labeo calbasu (Hamilton 1822) as a component of polyculture system - Bibha Chetia Borah; Rimzhim Gogoi; Abdur Rahman (Journal of Fisheries, 2014)
This paper deals with the performance of Labeo calbasu (Hamilton, 1822) as a component of conventional composite carp culture system. The species was included as 50% substitution to common carp (Cyprinus carpio) in view of its omnivorous feeding habit and bottom dwelling nature. The total production was 0.55% higher in the experimental culture (with L. calbasu and Cyprinus carpio) than in the control (common carp only). The difference in the production was however not significant statistically. The comparative economics revealed 5.30% higher return from the experimental unit. Comparison of growth pattern and survival rates of other five species of carps indicated that inclusion of L. calbasu did not have any adverse impact on the other carps. Growth rate of other carps was observed to be higher in the experimental set by 0.05% on an average than the control. Calculated profit per hectare was found to be 9.2% higher in experimental plot than in the control. Although the gross production and return in the experimental unit was not significantly higher than the control, the data supported that L. calbasu is compatible to other component species in composite carp culture system and its inclusion will enhance the economic viability of the system.